Penolakan Masyarakat Serangan Terhadap Kebijakan Desa Adat (Studi Kasus: Gerakan Penolakan Portal Retribusi Parkir Wisata SeranganTahun 2021) - Wijaya, I Made Putra; Apriani, Kadek Dwita; Erviantono, Tedi (Jurnal Nawala Politika; Vol 2 No 1 (2023): Jurnal Ilmu Politik, 2023)
This study attempts to describe how the rejection of the parking retribution portal in Serangan Village will be carried out in 2021. The author uses conflict theory to portray how Ralf Dahrendorf argues that conflict involves a struggle to obtain rare goods from a resource. This theory aptly describes that conflicting interest groups compete for power. In this research, we will examine in more depth the forms of resistance based on conflicts that occur between authorities and the public as the object of implementation of a policy. Methods This study used a qualitative method with a descriptive-explanative type of research in which data collection techniques were carried out using in-depth interviews with stakeholders in Serangan Village. From this study it was found that the rejection was made by two banjars which disputed the parking portal policy, which was in accordance with Ralf Dahrendorf's theory regarding the struggle for resources in this case study was the interest in the portal installation program in Serangan Village which occurred due to lack of socialization, inappropriate program implementation and there is a mismatch of communication between local policy makers. Keywords: Rejection, Conflict, Serangan Village